New, Dual-Anion Mechanism for Molten Carbonate Fuel Cells Working as Carbon Capture Devices. Issue 8 (27th April 2020) - Audasso, E.; Bosio, B.; Bove, D.; Arato, E.; Barckholtz, T.; Kiss, G.; Rosen, J.; Elsen, H.; Gutierrez, R. Blanco; Han, L.; Geary, T.; Willman, C.; et al.
Abstract : Molten Carbonate Fuel Cells (MCFCs) are commercially employed in MW-scale power production, and recently are being developed also for carbon capture. Past experiments showed that MCFC performance with wet cathode feeding was higher than with dry cathode feeds at otherwise similar conditions. This was ascribed to a mechanism that predicted the water increasing the apparent CO2 diffusion rate. However, recent tests performed at low CO2 cathode feed concentrations, as in carbon capture service, showed the emergence of a different water effect. Namely, there seems to be an electrochemical reaction path attributable to water, involving hydroxide ions that runs parallel with the main path involving CO2 . This results in lower CO2 transfer from the cathode to the anode than what can be calculated from the electrical current. For the first time, here, a theoretical analysis will be presented to introduce a kinetic expression for MCFCs working under this dual-ion regime. Focus will be given to the expression of CO2 and water polarization to assess the ratio between the current due to the two anions. Simulation and experimental results will be discussed providing a reliable and effective basis for the performance optimization of the MCFCs both in power and in carbon capture applications.